'Savoir Fare': Are cooking skills a new morality? - Coveney, J.; Begley, Andrea; Gallegos, D. (Adult Learning Australia Inc, 2012)
There has been a recent surge of interest in cooking skills in a diverse range of fields, such as health, education and public policy. There appears to be an assumption that cooking skills are in decline and that this is having an adverse impact on individual health and well-being, and family wholesomeness. The problematisation of cooking skills is not new, and can be seen in a number of historical developments that have specified particular pedagogies about food and eating. The purpose of this paper is to examine pedagogies on cooking skills and the importance accorded them. The paper draws on Foucault’s work on governmentality. By using examples from the USA, UK and Australia, the paper demonstrates the ways that authoritative discourses on the know how and the know what about food and cooking – called here ‘savoir fare’ – are developed and promulgated. These discourses, and the moral panics in which they are embedded, require individuals to make choices about what to cook and how to cook, and in doing so establish moral pedagogies concerning good and bad cooking. The development of food literacy programmes, which see cooking skills as life skills, further extends the obligations to ‘cook properly’ to wider populations.The emphasis on cooking knowledge and skills has ushered in new forms of government, firstly, through a relationship between expertise and politics which is readily visible through the authority that underpins the need to develop skills in food provisioning and preparation; secondly, through a new pluralisation of ‘social’ technologies which invites a range of private-public interest through, for example, television cooking programmes featuring cooking skills, albeit it set in a particular milieu of entertainment; and lastly, through a new specification of the subject can be seen in the formation of a choosing subject, one which has to problematise food choice in relation to expert advice and guidance. A governmentality focus shows that as discourses develop about what is the correct level of ‘savoir fare’, new discursive subject positions are opened up. Armed with the understanding of what is considered expert-endorsed acceptable food knowledge, subjects judge themselves through self-surveillance. The result is a powerful food and family morality that is both disciplined and disciplinary.